A study of brand fidelity: Its contribution and impact on the Saudi market - Mohammad Rishad Faridi; Mohammad Naushad (Innovative Marketing)
The paradigm shift caused by disruption of traditional business models and innovation is among some factors which have propelled marketers forward-thinking in emphasizing brand fidelity. It is a novel idea and an innovative approach to understanding the impact of consumers while they demonstrate love and commitment through engagement, subconsciously or otherwise, with respect to cognition and behavior. The current study tested the components/factors of brand fidelity among Saudi consumers. The primary data for the study were collected based on the survey instrument among Saudi consumers. Overall, 446 responses were used to analyze the results. Exploratory factor analysis (EFA) coupled with confirmatory factor analysis (CFA) using IBM SPSS and AMOS were used to analyze the data. All the factors of brand fidelity, namely “accommodation/price”, “accommodation/performance”, “cognitive interdependence”, and “derogation of alternatives”, hold valid in the Saudi context with exploratory factor analysis with a factor loading of each factor above the threshold value of 0.50, and with confirmatory factor analysis with a threshold value of more than or equal to 0.60 for all the factor loadings. The result thus obtained suggests that the brand fidelity scale is valid in the Saudi context. Saudi consumers were found to be highly loyal to their favorite brands. The findings of the study will provide inputs to the companies operating in the Saudi market for their brand-related strategy formulation. Moreover, the paper indicates undermining the power of brand fidelity in improving the bottom line through experience management. AcknowledgmentThis paper was supported by the Deanship of Scientific Research at Prince Sattam Bin Abdulaziz University, Alkharj, Saudi Arabia, under the Specialized Research Grant program with Grant No. 2020/02/17342.